Ketidakpatuhan Australia Terhadap Antarctic Treaty dengan Penempatan Militer di Antartika - Fakhriza Naufal Rakin; Satwika Paramasatya (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2022)
This study aims to explain Australia's non-compliance with the Antarctic Treaty regime that they had previously ratified by placing military technology on the